The Republic Electoral Commision as the fourth branch of government – challenges and perspectives - Stamenković, Viktor (Sociološki pregled, 2024)
This paper analyzes the current status of the Republic Electoral Commission (RIK) and emphasizes the need for change so as to transform it from an existing partisan body with weak capacities into a more neutral, stronger, and more independent institution. Based on solutions from comparative practices, several measures that can be taken on this path are proposed. Firstly, it is necessary to change the current method of electing RIK members in order to reduce partisan influence on this body. Additionally, extending the term of office for RIK members is required to ensure greater independence of RIK from the current configuration of political forces and provide the opportunity for fundamental and concrete steps towards improving the electoral process. Activities related to elections, currently carried out by several other bodies in addition to RIK, should be centralized and entrusted to a professional electoral administration in order to eliminate unnecessary communication between RIK and these bodies. This would make the entire process of organizing and monitoring elections more simpler and coherent. Implementing these solutions could lead to RIK becoming a game changer in contexts of weakened institutional capacities and a limited number of external factors that can influence the improvement of the democratic process, contributing to freer and fairer elections.